Peran Perawat dalam Deteksi Dini Kanker Serviks Melalui Program PAP Smear pada Wus di Poli Kebidanan RSUD Karawang - Dewi, Nunik Kurnia; Hardiati, Iis Sri (Universitas Malahayati, 2025)
ABSTRACT Cervical cancer is one of the number one causes of death caused by cancer in women in developing countries. Cervical cancer cases in Indonesia increased to 36,633 (17.2%) with 234,511 deaths. Cervical cancer cases can actually be prevented in several ways, one of which is early detection with the pap smear method and also supported by nurse support when undergoing a screening procedure with the pap smear method. The support of nurses as health workers is also an important role in increasing women's interest or willingness to carry out early detection examinations with the pap smear method. To analyze the role of nurses in women of childbearing age in decision-making for early detection of cervical cancer by the pap smear method. This research was conducted with a quantitative approach, with a cross sectional research design. Sampling was taken by Simple Random Sampling of 24 people. The quantitative approach analysis was carried out using frequency distribution for univariate analysis and T-test test for bivariate analysis. The relationship between the role of nurses and decision-making in women of childbearing age in carrying out pap smears is seen from the results of the T-test test of 0.467 with a p-value of 0.000 which means that there is a significant relationship between the role of nurses and decision-making in women of childbearing age in early detection with the pap smear method.From the results of the study, it is known that there is a significant influence between the role of nurses or health worker support in the decision-making of women of childbearing age in early detection of cervical cancer using the pap smear method. The majority of women of childbearing age have a supportive attitude towards the implementation of pap smear as much as 83.3%, full support from health workers, especially nurses as much as 100%, and the implementation of pap smear for women of childbearing age as much as 58.3%. Keywords: Cervical cancer, Pap Smear, Nurse Support ABSTRAK Kanker serviks merupakan salah satu penyebab kematian nomor satu yang disebabkan oleh kanker pada wanita di negara berkembang. Kasus kanker serviks di Indonesia meningkat berjumlah 36,633 (17,2%) dengan kematian sejumlah 234.511. Kasus kanker serviks sebenarnya dapat dicegah dengan melakukan beberapa cara salah satunya dengan deteksi dini dengan metode pap smear dan juga ditunjang dengan dukungan perawat saat menjalani prosedur skrining dengan metode pap smear. Dukungan perawat sebagai tenaga kesehatan juga merupakan suatu peran penting dalam meningkatkan minat atau kemauan wanita untuk melakukan pemeriksaan deteksi dini dengan metode pap smear.Untuk menganalisis peran perawat pada wanita usia subur dalam pengambilan keputusan deteksi dini kanker serviks dengan metode pap smear. Penelitian ini dilakukan dengan pendekatan kuantitatif, dengan rancangan penelitian cross sectional. Pengambilan sampel diambil secara Simple Random Sampling sebanyak 24 orang. Analisis pendekatan kuantitatif dilakukan dengan menggunakan distribusi frekuensi untuk analisis univariat dan uji T-test untuk analisa bivariat. Adanya hubungan antara peran perawat dengan pengambilan keputusan wanita usia subur dalam melaksanakan pap smear dilihat dari hasil uji T-test sebesar 0,467 dengan p-value 0,000 yang berarti adanya hubungan yang signifikan antara peran perawat dengan pengambilan keputusan pada wanita usia subur dalam deteksi dini dengan metode pap smear. Dari hasil penelitian diketahui adanya pengaruh yang signifikan antara peran perawat atau dukungan tenaga kesehatan pada pengambilan keputusan wanita usia subur dalam melakukan deteksi dini kanker serviks menggunaan metode pap smear. Mayoritas wanita usia subur memiliki sikap yang mendukung pada pelaksanaan pap smear sebanyak 83,3%, dukungan penuh dari tenaga Kesehatan khususunya perawat sebanyak 100%, dan pelaksanaan pap smear pada wanita usia subur sebanyak 58,3%. Kata Kunci: Kanker serviks, Dukungan Perawat, Pap Smear